Beekeepers get the 'BEST' help - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Beekeepers in Southern Belize who formed a cooperative in 1980 are now working together with BEST (Belize Enterprise for Sustained Technology) to improve production consistency. The Southern Beekeepers Cooperative Society Ltd was born as a solution...